Isolation and Characterization of Two New Secondary Metabolites From Quercus incana and Their Antidepressant- and Anxiolytic-Like Potential - Sarwar, Rizwana; Farooq, Umar; Naz, Sadia; Khan, Ajmal; Bukhari, Syed M.; Khan, Haroon; Karim, Nasiara; Khan, Imran; Ahmed, Ayaz; Al-Harrasi, Ahmed (Frontiers in Pharmacology, 2018)
The ethyl acetate fraction of Quercus incana yielded two new compounds [1 and 2]. The characterization and structure elucidation of these compounds were carried out through various spectroscopic techniques such as mass spectrometry along with one and two-dimensional NMR techniques. The structural formula were deduced to be 2-(4-hydroxybutan-2-yl)-5-methoxyphenol [1] and 4-hydroxy-3-(hydroxymethyl) pentanoic acid [2]. The elevated plus maze (EPM) and light dark box (LDB) tests (classical mouse models) were performed in order to reveal the anxiolytic potential of both compounds [1 and 2]. Both compounds displayed dose dependent increases in open arm entries and time spent in open arms in EPM (*P<0.05, **P<0.01), and increased the time spent in the lit compartment and increased transitions between the two compartments in LDB test (*P<0.05, **P<0.01). Co-administration of selective benzodiazepine receptor antagonist, flumazenil (2.5 mg/kg) with compounds [1 and 2] decreased the anxiolytic-like activity of both compounds in the EPM indicating benzodiazepine binding site of GABA-A receptors are involved in the anxiolytic-like effect. Similarly, both compounds at the dose level of 10 and 30 mg/kg, i.p. exerted pronounced antidepressant-like effect in both forced swimming as well as tail suspension tests (*P<0.05, **P<0.01; ANOVA followed by Dunnett’s posthoc test). The effect at 30 mg/kg was comparable to the reference drug imipramine (60 mg/kg).